PENGEMBANGAN BUSANA BERSILUET H DENGAN HIASAN 3D - Faida Suci Wulandari; Sugiyem Sugiyem (Jurnal Da Moda, 2023)
The purpose of this study was to develop party wear and find out the preferences of female consumers on H silhouette party dresses with 3D sequin decorations. This research is a Research & Development research. This study uses the 4D Thiagarajan development model, namely: define, design, development, and dissemination. The data collection method in this study was an online Google form questionnaire with 52 respondents. Data analysis techniques using descriptive statistics. The results of the study were: 1) The realization of an H-silhouette party dress made of satin and organza with 3D sequin decoration, 2) Consumer preference test for party dresses 90.4% were very interested in the 3D form of decoration on party clothes, 87.7% of respondents were interested in the placement decoration, 83% of respondents were interested in the choice of satin and organza, 82.7% of respondents were interested in the H silhouette of party dresses, and 81.5% of respondents were interested in the use of white bones in party dresses.